Asgard Stories: Tales from Norse Mythology - Foster, Mary H.; Cummings, Mabel H. (Mabel Homer), 1872-1962 (Salt Lake City, UT : Project Gutenberg, 2011)
"Asgard Stories: Tales from Norse Mythology" by Mary H. Foster and Mabel H. Cummings is a collection of children's stories written in the early 20th century. This anthology focuses on Norse mythology, distilling complex tales into simpler narratives suitable for young readers. It aims to introduce children to the enduring themes and characters from Norse legends, including gods like Odin, Thor, and Loki, as well as the nature of their adventures and interactions." "The opening of this collection sets a stage for the rich world of Norse mythology, explaining how ancient Northern peoples created stories around natural phenomena they observed. The authors introduce Odin, the Allfather, and the origins of the world as conceived by these peoples, complete with elemental forces like giants and deities. It further explains the notion of different realms such as Asgard and Midgard and the connections between them, hinting at the stories to come that will explore these characters and their exploits, inviting readers on a fantastical journey through Nordic tales." (This is an automatically generated summary.)
Release date is 2011-09-20
E-text prepared by Juliet Sutherland, eagkw, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Mythology, Norse; Eddas -- Translations into English